2022
DOI: 10.3390/ijms232214318
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Major Effector StSROs in Potato: A Potential StWRKY-SRO6 Regulatory Pathway Enhances Plant Tolerance to Cadmium Stress

Abstract: SIMILAR TO RCD-ONE (SRO) family members and transcription factors (TFs) often improve plant antioxidant capacity through interaction and co-regulation and participate in plant resistance to drought and high-salt stress. However, whether SROs are involved in the response to heavy metal stress, especially SRO genes with a specific response and tolerance characteristics to cadmium (Cd) stress, remains unclear. We first identified six SRO genes in the potato genome by PARP and RST domains. Special and conserved St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Particularly, the SRO family plays an important role in response to abiotic stresses such as salt and drought [ 3 ]. In addition to a poly (ADP-ribose) polymerase catalytic center (PARP, PS51059), SROs usually contain the RCD1-SRO-TAF4 structural domain (RST, PF12174) that interacts with other transcription factors (TFs) [ 4 ]. Some SROs also contain the N-terminal WWE (PS50918) structural domain, which is involved in ADP ribosylation (ADPRylation) and protein ubiquitination [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the SRO family plays an important role in response to abiotic stresses such as salt and drought [ 3 ]. In addition to a poly (ADP-ribose) polymerase catalytic center (PARP, PS51059), SROs usually contain the RCD1-SRO-TAF4 structural domain (RST, PF12174) that interacts with other transcription factors (TFs) [ 4 ]. Some SROs also contain the N-terminal WWE (PS50918) structural domain, which is involved in ADP ribosylation (ADPRylation) and protein ubiquitination [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…They can recruit other transcriptional regulatory factors and RNA polymerases to form a transcriptional complex, thereby promoting or inhibiting the transcription of downstream genes [ 2 , 3 ]. Based on our previous research, we found that the expression of the potato ( Solanum tuberosum ) WRKY6 gene was closely related to plant tolerance to cadmium (Cd), suggesting its possible involvement in regulating the accumulation of Cd in plants [ 4 , 5 ]. Cd is a toxic heavy metal that widely exists in the natural environment.…”
Section: Introductionmentioning
confidence: 99%